Prinsip Pengembangan Media Pembelajaran Berbasis Edmodo Bagi Guru Pendidikan Agama Islam - Asmuki (Universitas Yudharta Pasuruan, 2021)
The development of science and technology is increasingly rapid today. This has an impact on aspects of education, especially the competence of teachers who must follow the development of rapidly developing technology. But in fact there are still many competencies of teachers, especially in the field of Islamic religious education that experience obstacles in the field of Information, Communication and Technology, such as developing learning media. This paper aims to explain the principles in developing an Edmodo-based learning medium for Islamic religious education teachers. Learning media has benefits including being able to awaken student learning motivation. Some of the benefits of Edmodo in learning one of them is to provide a means for students, teachers and parents to communicate actively.